Design of LMS Framework to Modernize Pharma Talent Development for the Future Job Market - Nate, Chandra (Global journal of Business and Integral Security, 2024)
This research is the result of the efforts of an enterprise company that was founded in the year 2000. The company has a specialization in providing highly targeted and role-specific training programs in the field of pharmaceuticals. These programs are designed to cater to the specific needs and requirements of various roles within the pharmaceutical industry. The company's primary focus areas include clinical research and trial management, drug safety and pharmacovigilance, and clinical data management. In the year 2015, the company conducted a comprehensive survey in collaboration with its stakeholders, which included pharmaceutical professionals, educators, industry experts, and other key players in the pharmaceutical sector. The purpose of this survey was industry insights into the current state of pharmaceutical training programs and the challenges faced by individuals seeking careers in the industry. The survey was structured to encompass a wide range of topics, including the effectiveness of existing training programs, industry demands, emerging technologies, and the gap between theoretical knowledge and practical application. The main objective of this research initiative was to develop a cutting-edge Learning Management System (LMS) tailored specifically for pharmaceutical education. This LMS was envisioned to serve as a revolutionary platform that would address numerous challenges faced by both educators and learners in the pharmaceutical field. The key objectives and outcomes of this research are as follows: The culmination of this research endeavor is the development of a forward-thinking and transformative Learning Management System (LMS) tailored specifically for pharmaceutical education. This LMS is designed to address a myriad of challenges faced by educators and learners in the pharmaceutical sector while aligning training programs with the ever-evolving demands of the industry. Here are the key components of the research outcomes and proposed solutions: P a g e 4 | 263 Enhancing LMS for Practical Application: The research involves a comprehensive approach to enhance the LMS for practical application. This begins with a needs assessment and gap analysis to identify areas where current training programs fall short in linking theoretical knowledge to real-world scenarios. To bridge this gap, the LMS will incorporate practical modules, virtual labs, and industry collaborations. Learners will benefit from adaptive learning paths, and learning analytics will provide insights into their progress. Additionally, cutting-edge technologies such as Artificial Intelligence (AI), Augmented Reality (AR), and Virtual Reality (VR) will be integrated to create immersive learning experiences. Continuous evaluation and faculty training programs will ensure the effectiveness of these enhancements. Realigning Training with Industry Demands: To ensure that pharmaceutical training programs remain relevant and responsive to industry demands, the research proposes a rigorous industry analysis. This analysis will inform curriculum evaluation and enhancement efforts, ensuring that learners are exposed to the latest advancements and trends in the pharmaceutical field. Emerging technologies will be seamlessly integrated, experiential learning opportunities will be provided, and faculty members will receive ongoing development to keep them up-to-date. The establishment of industry advisory boards will foster collaboration between academia and the pharmaceutical sector, helping to bridge the gap between theory and practice. Continuous assessment and feedback mechanisms will play a pivotal role in maintaining alignment with industry needs. Customized Learning for Diversity: Recognizing the diverse backgrounds and career aspirations of learners in the pharmaceutical sector, the study places a strong emphasis on customized learning experiences. This includes the use of demographic profiling to better understand learners, curriculum customization to cater to individual needs, learner profiling to track progress and preferences, and personalized content recommendations. Mentorship programs will be established to provide guidance and support, and a variety of multimodal resources will be made available to accommodate different learning styles. Collaboration and privacy considerations will ensure that each learner's educational journey is tailored to their unique requirements. Role of AI and ML in Talent Development: The research delves into the pivotal role of Artificial Intelligence (AI) and Machine Learning (ML) in pharmaceutical talent development. This involves identifying specific use cases for AI and ML in the pharmaceutical context and P a g e 5 | 263 seamlessly integrating these technologies into the LMS. AI and ML will enable personalized learning experiences, advanced analytics, virtual labs, and ethical considerations will guide their implementation. Support for Fresh Graduates: Fresh graduates face unique challenges when entering the pharmaceutical industry. To support their transition, the research identifies these challenges and conducts skill gap analyses. Career development programs will be implemented to enhance graduates' employability, with a focus on developing essential soft skills. Career guidance, access to online resources, industry partnerships, and Post Training Assistance (PTA) will provide invaluable support. Continuous feedback and data-driven insights will ensure that these support programs remain effective and responsive to graduates' needs. In essence, this research serves as a strategic blueprint for the transformation of pharmaceutical education through the implementation of a cutting-edge LMS. These solutions are designed to meet the evolving needs of the industry, educators, and learners, ushering in a new era of pharmaceutical training and talent development.